2016
DOI: 10.1007/s00213-016-4323-9
|View full text |Cite
|
Sign up to set email alerts
|

Responses to drugs of abuse and non-drug rewards in leptin deficient ob/ob mice

Abstract: Rationale Although leptin receptors are found in hypothalamic nuclei classically associated with homeostatic feeding mechanisms, they are also present in brain regions known to regulate hedonic-based feeding, natural reward processing, and responses to drugs of abuse. The ob/ob mouse is deficient in leptin signaling, and previous work has found altered mesolimbic dopamine signaling and sensitivity to the locomotor activating effects of amphetamine in these mice. Objectives We directly assessed responses to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 67 publications
(90 reference statements)
1
13
0
Order By: Relevance
“…It should be noted that locomotor activity tends to be depressed in obese mice, probably due to abnormal neuroendocrine function [21]. Locomotor responses to systemic administration of 10 mg/kg cocaine was reduced in ob/ob mice, while conditioned place preference was increased by 2.5 mg/kg of cocaine [22]. These results contributed new important information about METH effects on females, extending our group’s previous report [14].…”
Section: Discussionsupporting
confidence: 63%
“…It should be noted that locomotor activity tends to be depressed in obese mice, probably due to abnormal neuroendocrine function [21]. Locomotor responses to systemic administration of 10 mg/kg cocaine was reduced in ob/ob mice, while conditioned place preference was increased by 2.5 mg/kg of cocaine [22]. These results contributed new important information about METH effects on females, extending our group’s previous report [14].…”
Section: Discussionsupporting
confidence: 63%
“…The fact that the lean and obese Zucker rats in the current report were comparable in cocaine self-administration, including acquisition, supports the conclusions of Wellman et al because both groups were fed the same standard diet. Similarly, a recent report found that ob/ob mice with deficient leptin-receptor signaling were no different than their lean, wild-type counterparts in self-administration of a dose of cocaine (0.5 mg/kg/inj) under fixed and progressive-ratio schedules of reinforcement (Muelbl et al, 2016), and these animals also had the same standard diet histories. In addition to changes in cocaine self-administration, exposure to a high-fat diet has been reported to enhance the locomotor-stimulating effects of cocaine in adolescent male (Baladi et al, 2012), but not adult male or female (Baladi et al, 2012; Serafine et al, 2014) rats.…”
Section: Discussionmentioning
confidence: 92%
“…Recent pre-clinical reports provide emerging mechanistic evidence for the role of leptin in reward functioning beyond food-related hedonic capacity. Central or peripheral leptin administration significantly attenuates cocaine-mediated reward processing ( 13 ), while obese, leptin-deficient ob/ob mice exhibit abnormal responses to standard reward tasks and to drugs of abuse (cocaine, opioids, and ethanol) compared to wild-type mice ( 14 ), suggesting leptin’s blunting of reward capacity may extend to non-food substances and other primary rewards. The extent to which these functions systematically differ according to fat mass have not been well-explored in humans.…”
Section: Discussionmentioning
confidence: 99%